2014
DOI: 10.1007/s00167-014-3117-z
|View full text |Cite
|
Sign up to set email alerts
|

A cadaveric study of the anterolateral ligament: re-introducing the lateral capsular ligament

Abstract: From this study, the ALL is an independent structure in the anterolateral compartment of the knee and may serve a proprioceptive role in knee mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
364
1
46

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(441 citation statements)
references
References 36 publications
30
364
1
46
Order By: Relevance
“…9,13 Placement for the femoral position is crucial to obtain appropriate isometry; however, the location of the femoral origin is debatable. Claes et al 1 reported an attachment anterior to the lateral collateral ligament (LCL); Helito et al 2 described an anterior and distal insertion to the LCL; Dodds et al 3 described a more proximal and posterior insertion to the LCL; and Caterine et al 4 reported significant variability in the femoral insertion, being posterior and proximal to anterior and distal to the LCL. A recent biomechanical study by Kittl et al 9 determined that for an extraarticular lateral reconstruction, the most isometric femoral insertion would be proximal to the lateral epicondyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13 Placement for the femoral position is crucial to obtain appropriate isometry; however, the location of the femoral origin is debatable. Claes et al 1 reported an attachment anterior to the lateral collateral ligament (LCL); Helito et al 2 described an anterior and distal insertion to the LCL; Dodds et al 3 described a more proximal and posterior insertion to the LCL; and Caterine et al 4 reported significant variability in the femoral insertion, being posterior and proximal to anterior and distal to the LCL. A recent biomechanical study by Kittl et al 9 determined that for an extraarticular lateral reconstruction, the most isometric femoral insertion would be proximal to the lateral epicondyle.…”
Section: Discussionmentioning
confidence: 99%
“…R ecently, authors have reported the anatomic and functional characteristics of the anterolateral ligament (ALL), [1][2][3][4] describing a structure that originates near the lateral epicondyle on the femur and inserts broadly in a fan-like attachment on the tibia between the Gerdy tubercle and the fibular head. 5 Functionally, the ALL is an important stabilizer of the knee, serving as the primary restraint to internal rotation of the tibia throughout varying degrees of knee flexion.…”
mentioning
confidence: 99%
“…21 Regarding the relationship to the lateral collateral ligament (LCL), the ALL is described as being superficial to the LCL. 22 Many ALL reconstruction techniques have used a graft passing deep to the LCL, which could explain the over-tightening and the sub-optimal results seen with these methods. 23 Other researchers consider that the ALL and the deep capsulo-osseous fibers of the iliotibial tract are in fact one and the same structure.…”
Section: Capsular Versus Extracapsularmentioning
confidence: 99%
“…Recent publications advocating a newly discovered anterolateral ligament [97][98][99][100] have led to a re-examination of the anatomy and biomechanical function of the anterolateral complex of the knee (see Fig. 4).…”
Section: Associated Soft Tissue Injuriesmentioning
confidence: 99%